Implementation of the problem-based learning model assisted by web-based practical media simulation on students’ metacognitive abilities and activeness - Karlina; Puspitasari, Etika Dyah; Fika Enggar Prayogo (Universitas Ahmad Dahlan, 2025)
Metacognition plays a crucial role in regulating and controlling students' cognitive processes in learning, thinking, and problem-solving. Teachers have not yet assessed students' metacognitive abilities. In biology learning at SMAN 1 Ngemplak, teachers focus more on theory, resulting in suboptimal student engagement. One factor is the less engaging learning activities, resulting in students being more interested in using their mobile phones than in the teacher. This study aimed to determine the effect of the PBL model supported by web-based simulation media on students' metacognition in the digestive system and student engagement. This study employed a quasi-experimental design with a pretest-posttest approach. The population consisted of 65 students from class XI MIPA at SMAN 1 Ngemplak (two classes), and the sample used was saturated. Data collection was conducted through observation and tests, utilizing research instruments that included student engagement observation sheets and test question sheets. The data analysis techniques used were descriptive and inferential. The hypothesis test used was the Mann-Whitney U test. The results of this study showed a significant value of p < 0.05, indicating that there is no influence of the PBL model assisted by web-based practical media simulation on students' metacognitive abilities. The findings imply that while PBL combined with web-based simulation enhances student engagement, it does not significantly improve metacognition. Therefore, educators should complement this approach with explicit metacognitive training to develop students’ cognitive regulation skills. Integrating interactive media with strategies targeting metacognition can create more balanced and effective biology learning experiences.